TERAPI RELAKSASI GUIDED IMAGERY DALAM ASUHAN NYERI HAID (DISMENORE) PRIMER PADA MAHAMAHASISWI D3 KEBIDANAN UNIVERSITAS BHAKTI KENCANA - Dewi Nurlaela Sari; Deva Frisilya (LPPM Universitas Abdurrab, 2020)
Adolescence (adolence) is a period of transition from childhood to adulthood with the age limit of 10 to 18 years or before marriage which generally occurs in puberty, namely the process of changes in physical maturity. Physical or biological changes in young women are starting to experience menstruation. One complaint that usually occurs in women who are menstruating is dysmenorrhea . One way that can be done to reduce pain is by relaxation (guided imagery). This study aims to determine whether there is an effect of guided imagery relaxation therapy by decreasing the level of pain in primary dysmenorrhea in diploma of midwefery. The type of method used is quasy experiment with approach one group pre-post test design. The sampling method with probability sampling with a total sample of 51 respondents. The instrument used is NRS (numeral rating scal ) and SOP of guided imageryrelaxation therapy. The type of univariate analysis used frequency distribution and bivariate analysis using paired t test analysis. The results of this study indicate that guided imagery relaxation therapy is effective in reducing the scale of menstrual pain ( dysmenorrhea ) in diploma of midwefery, the results of statistical tests using the Wilcoxon test obtained with a significant value of p-value (2-tailed) 0,000 (p < 0.05). The conclusion of this study is that there is a significant effect of guided imagery relaxation therapy on decreasing the level of menstrual pain (dysmenorrhea) in adolescent girls. Based on the above research, guided imagery relaxation therapy can be applied as one of the non-pharmacological pain management during menstruation (dysmenorrhea).